2012
DOI: 10.5851/kosfa.2012.32.5.545
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NaCl on Thermal Resistance, Antibiotic Resistance, and Human Epithelial Cell Invasion of Listeria monocytogenes

Abstract: This study evaluated the effects of NaCl on heat resistance and Caco-2 cell invasion of Listeria monocytogenes in broth media and sausage. A 10-strain mixture of L. monocytogenes was inoculated in tryptic soy broth containing 0.6% yeast extract (TSBYE), and sausage formulated with 0, 2, 4, and 6% NaCl. The medium was stored at 7, 15, 20, and 25 o C for 3-16 d, and medium samples were withdrawn at the appropriate time and challenged to 55, 60, and 63 o C to evaluate the thermal resistance of the pathogen. Sau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…For Staphylococcus aureus , exposure to NaCl increased its thermal resistance in ready-to-heat sauces [8]. Other studies also showed that the exposure of bacteria to sublethal stresses such as acid, heat, and NaCl increased their cross-protection responses, especially following continuous exposure to the stresses [9, 10]. A study by Kieboom et al [11] revealed that S .…”
Section: Introductionmentioning
confidence: 99%
“…For Staphylococcus aureus , exposure to NaCl increased its thermal resistance in ready-to-heat sauces [8]. Other studies also showed that the exposure of bacteria to sublethal stresses such as acid, heat, and NaCl increased their cross-protection responses, especially following continuous exposure to the stresses [9, 10]. A study by Kieboom et al [11] revealed that S .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it can be suggested that the effect of NaCl on increasing the thermal resistance of E. coli is strain‐dependent, as suggested by Lee et al . () and Lianou et al . ().…”
Section: Resultsmentioning
confidence: 87%
“…However, the invasion efficiency of the NS and HS L. monocytogenes strains in Caco-2 cells was not different (data not shown). Lee et al (2012) also showed that exposure to NaCl did not affect human epithelial cell invasion of L. monocytogenes . These results indicate that there may be a threshold for inlA and inlB gene expression required for efficient L. monocytogenes invasion, and invasion efficiency may not be affected by inlA and inlB expression above the threshold.…”
Section: Resultsmentioning
confidence: 92%
“…grown in liquid egg yolk containing 10% salt was higher than that in plain egg yolk ( Palumbo et al , 1995 ). Lee et al (2012) demonstrated that a mixture of 10 L. monocytogenes strains habituated by NaCl showed heat resistance, especially when they were exposed to sequentially higher NaCl concentrations (0%, 2%, 4%, and 6%). Kotrola and Conner (1997) showed that NaCl exposure increased the D -value of E. coli O157:H7 when grown at 52℃, 55℃, 57℃, and 60℃, indicating the increased survival of the bacterium.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation